Prevalence of Restless Legs Syndrome in Iranian Patients under Hemodialysis: A Systematic Review and Meta-Analysis Study - Mohammad Hossein Sorbi; Bahareh Baharvand; Fatemeh Dehghanniry; Mohammad Reza Gol Mohammadi Shooroki; Melina Jafarzadeh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2022)
Introduction: Recent studies have contradictory reports of the overall prevalence of restless legs syndrome in hemodialysis patients. Therefore, the aim of this study was to help eliminate ambiguity about the prevalence of restless legs syndrome in Iranian hemodialysis patients by systematic review and meta-analysis study. Methods: This study was performed based on PRISMA checklist. Documents were obtained from English and Persian databases such as Magiran, Sid, Medilib, Iranmedex, Irandoc, CIVILICA, ISC, Pubmed, Scopus, Springer, and Google Scholar Engine from 2000 to 2021. All reviewed articles with selection criteria were evaluated qualitatively with the STROBE checklist. Comprehensive Meta-analysis (CMA-2) software was used to analyze the data by meta-analysis random effects method. Results: Prevalence of restless legs syndrome in the patients under hemodialysis was estimated to be 49.6% (95% CI: 39.9-59.3) in 13 studies with 2431 Iranian samples that 62.3% of whom were men. The prevalence of this disorder was 54.2% in Iranian women (95% CI: 41.7-66.3) and 43.5% in Iranian men (95% CI: 31.6-56.3). The most and least prevalence of restless legs syndrome in hemodialysis patients was respectively in Yazd (66.4%) and in Tehran (35.3%). In addition, regression analysis showed that there was a significant relationship between sex, urban areas, sample size and age of patients with restless legs syndrome. Conclusion: The prevalence of restless legs syndrome is high in Iranian hemodialysis patients, which early diagnosis, prevention and treatment of this disorder in adults seems necessary.